Assessment of management and collection of zoological specimens at natural history Museums in Malaysia - Sapaat, Arney (2020)
There are many causes contributing to biodiversity loss and lack of understanding on the importance of natural history collections is one. Ineffective dissemination of biodiversity knowledge, poor maintenance of natural history collection and lack of understanding as perceived by Malaysian why the need for a natural history museum are problems answered by this research. This study aims, firstly, rationalize natural history collections as a tool in mainstreaming biodiversity in Malaysia, and secondly, to provide a guideline on maintaining biological specimens critical to their management. Data collection was done by gathering qualitative data from the field through study visits, interviews, questionnaires as well as experiments. Eleven institutions in Malaysia and each from Singapore, Indonesia, and Thailand were visited, and found having similar problems in managing zoological collection. From this study, the reason why Malaysia did not excel in the collection management was not because of the curators aptitude, but more to other factors that influencd the quality of collections management, such as funding and human resource. For the second objective, lack of awareness on biodiversity among Malaysian made them incapable to see the need to establish a natural history museum. A study case done to Natural History repository, Universiti Tun Hussein Onn identified Aspergillus sp., Chaetomium sp. and Mucor sp. were present on bat skin and entomological specimens used in this study. Invertebrate pests, Vollenhovia sp. and Dermatophagoides sp. were circumstantially found. However sign of insect activities such frass, shed skins and other body parts are actual evidences of insect pest occurrence. The low temperature and alcohol treatment proved to be the best non-pesticidal methods for remediation of zoological collections. Data from curators and case study were compiled into management practice for the care of zoological collections.